Gender-responsive rural climate services: a review of the literature - Gumucio, Tatiana; Hansen, James; Huyer, Sophia; Huysen, Tiff van (Informa UK Limited, 2020)
The review assesses the empirical knowledge base on gender-based differences in access, use and benefits from rural climate services to analyse gender equality challenges and identify pathways for making climate services more responsive to the needs of rural women and men. While existing research is limited, the review identifies key gender-related factors and processes that influence inequalities in access and use. Differential access to group processes and to Information and Communications Technologies (ICTs) can significantly limit women’s access to weather and climate information. Moreover, socio-cultural norms that define women’s and men’s labour roles can also influence the resources and decisions under women’s and men’s control, affecting their differing climate information needs and demand. Ways forward suggested by the literature concern inclusion of women’s groups and networks in communication channels and development of ICTs that respond to women’s preferences. Furthermore, meeting women’s climate information needs and pursuing cross-sectoral collaboration will be important to enhance action on climate information. Research opportunities include analyses of the potential for women’s and mixed-gender groups to enhance women’s access to climate information; evaluation of the communication processes that improve women’s understanding of climate information; and further connection with the body of knowledge on intra-household decision-making processes.